Yield optimisation of hepatitis B virus core particles in e. coli expression system for drug delivery applications - Mohamed Suffian, Izzat Fahimuddin; Garcia-Maya, Mitla; Brown, Paul; Bui, Tam; Nishimura, Yuya; Mohammad Johari Palermo, Amir Rafiq; Ogino, Chiaki; Kondo, Akihiko; Al-Jamal, Khuloud (Nature Publishing Group, 2017)
An E. coli expression system offers a mean for rapid, high yield and economical production of Hepatitis B Virus core (HBc) particles. However, high-level production of HBc particles in bacteria is demanding and optimisation of HBc particle yield from E. coli is required to improve laboratory-scale productivity for further drug delivery applications. Production steps involve bacterial culture, protein isolation, denaturation, purification and finally protein assembly. In this study, we describe a modified E. coli based method for purifying HBc particles and compare the results with those obtained using a conventional purification method. HBc particle morphology was confirmed by Atomic Force Microscopy (AFM). Protein specificity and secondary structure were confirmed by Western Blot and Circular Dichroism (CD), respectively. The modified method produced ∼3-fold higher yield and greater purity of wild type HBc particles than the conventional method. Our results demonstrated that the modified method produce a better yield and purity of HBc particles in an E. coli-expression system, which are fully characterised and suitable to be used for drug delivery applications.